Metabolomic Profiling Analysis of Physiological Responses to Acute Hypoxia and Reoxygenation in Juvenile Qingtian Paddy Field Carp Cyprinus Carpio Var Qingtianensis - Jiang, Yuhan; Qi, Ming; Zhang, Jinpeng; Wen, Yuanlin; Sun, Jiamin; Liu, Qigen (Frontiers in Physiology, 2022)
The Qingtian paddy field carp (Cyprinus carpio var qingtianensis) is a local carp cultivated in the rice field of Qingtian county, Zhejiang province, China. The paddy field environment is distinct from the pond environment. Due to the inability to artificially increase oxygen, the dissolved oxygen greatly changes during the day. Therefore, investigating the physiological regulation to the changes of acute dissolved oxygen in Qingtian paddy field carp (PF-carp) will dramatically clarify how it adapts to the paddy breeding environment. The high tolerance of Qingtian paddy field carp to hypoxia makes it an ideal organism for studying molecular regulatory mechanisms during hypoxia process and reoxygenation following hypoxia in fish. In this study, we compared the changes of metabolites in the hepatopancreas during hypoxia stress and the following reoxygenation through comparative metabolomics. The results showed 131 differentially expressed metabolites between the hypoxic groups and control groups. Among them, 95 were up-regulated, and 36 were down-regulated. KEGG Pathway enrichment analysis showed that these differential metabolites were mainly involved in regulating lipid, protein, and purine metabolism PF-carps could require energy during hypoxia by enhancing the gluconeogenesis pathway with core glutamic acid and glutamine metabolism. A total of 63 differentially expressed metabolites were screened by a comparison between the reoxygenated groups and the hypoxic groups. Specifically, 15 were up-regulated, and 48 were down-regulated. The KEGG Pathway enrichment analysis supported that PF-carp could continue to gain energy by consuming glutamic acid and the glutamine accumulated during hypoxia and simultaneously weaken the ammonia-transferring effect of amino acids and the toxicity of ammonia. By consuming glycerophospholipids and maintaining the Prostaglandin E content, cell damage was improved, sphingosinol synthesis was reduced, and apoptosis was inhibited. Additionally, it could enhance the salvage synthesis and de novo synthesis of purine, reduce purine accumulation, promote the synthesis of nucleotide and energy carriers, and assist in recovering physiological metabolism. Overall, results explained the physiological regulation mechanism of PF-carp adapting to the acute changes of dissolved oxygen at the metabolic level and also provided novel evidence for physiological regulation of other fish in an environment with acute changes in dissolved oxygen levels.